Determinan Kinerja Karyawan PT. Pegadaian Nusa Penida - Ni Made Satya Utami; Ni Putu Lina Dewiyanti; Anak Agung Putu Agung (CV. Kalimasada Group, 2025)
In this situation, issues related to employee performance are a central component of human resource management that must receive special attention. HR top management must carefully consider problems related to employees’ work. This study examines the impact of benefits, incentives, and the work environment on employee productivity at PT. Pegadaian (Persero) Nusa Penida. A saturated sampling technique was applied in a quantitative survey of the total population of 34 employees. After the data were collected through observation, interviews, and questionnaires, multiple linear regression analysis was performed using SPSS software. The findings suggest that the work environment and employee motivation have a positive and significant impact on their performance, whereas benefits and incentives have a limited influence. The results indicate that the work environment and motivation factors are essential to improving human resource productivity. This study suggests that management should focus on enhancing employee motivation and creating a pleasant work environment to achieve sustainable organizational growth.